Upaya Meningkatkan Hasil Belajar IPS Dengan Menggunakan Strategi Pembelajaran Bowling Kampus Peserta Didik: Efforts to Improve Social Studies Learning Outcomes by Using the Campus Bowling Learning Strategy for Students - Ahmad Effendi (Neraca: Jurnal Pendidikan Ekonomi, 2023)
This study aims to: (1) To describe student activities using the bowling strategy, (2) To describe teacher teaching activities using the bowling strategy, (3) To improve social studies learning outcomes using the bowling strategy, (4) To find out the implementation learning that is used when learning is carried out in social studies using a bowling strategy. This type of research is classroom action research, which is carried out in one cycle, the cycle consists of 4 stages, namely planning, action, observation, and reflection. The instruments used consisted of observation sheets and tests. Data collection techniques using observation, and learning achievement tests. Data analysis uses the average value and percentage of classical learning completeness. The results showed that: (1) increasing learning activities: (a) teacher activity in cycle I obtained an average of 3.64 with good criteria, (b) student activity in cycle I obtained an average of 3.75 with good criteria , (c) The implementation of learning in cycle I obtained an average of 3.67 with good criteria. (2) Improving learning outcomes: (a) Pre-cycle gets an average of 58.15 with a percentage of 18.5%, (b) Cycle I gets an average of 86.30 with a percentage of 100%